2021
DOI: 10.3389/fcell.2021.621482
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Non-syndromic Orofacial Clefts in a Multiethnic Sample of Families and Controls Identifies Novel Regions

Abstract: Orofacial clefts (OFCs) are among the most prevalent craniofacial birth defects worldwide and create a significant public health burden. The majority of OFCs are non-syndromic and vary in prevalence by ethnicity. Africans have the lowest prevalence of OFCs (~ 1/2,500), Asians have the highest prevalence (~1/500), Europeans and Latin Americans lie somewhere in the middle (~1/800 and 1/900, respectively). Thus, ethnicity appears to be a major determinant of the risk of developing OFC. The Pittsburgh Orofacial Cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Finally, the observed EAF within cases from the two GWASs were examined to assess whether these differed significant between cleft subtypes. We have previously shown that ancestry impacts association to CL/P in our POFC sample (Mukhopadhyay et al, 2021); therefore, we examined the subtype-specific effect sizes within each ancestry group to assess whether the differences observed were similar to the those observed for the meta-analysis. EAFs within cases were also compared across the eight phenotypic subtypes within each ancestry group in addition to the cases pooled across ancestry groups for each phenotypic subset.…”
Section: Comparison Of Association Outcomes Between Subtypesmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, the observed EAF within cases from the two GWASs were examined to assess whether these differed significant between cleft subtypes. We have previously shown that ancestry impacts association to CL/P in our POFC sample (Mukhopadhyay et al, 2021); therefore, we examined the subtype-specific effect sizes within each ancestry group to assess whether the differences observed were similar to the those observed for the meta-analysis. EAFs within cases were also compared across the eight phenotypic subtypes within each ancestry group in addition to the cases pooled across ancestry groups for each phenotypic subset.…”
Section: Comparison Of Association Outcomes Between Subtypesmentioning
confidence: 91%
“…We have shown previously that the degree of OFC risk at certain susceptibility loci varies with ancestry of the sample participants (Mukhopadhyay et al, 2021). To control for this variance, we first classified subjects into four different genetically defined ancestry groups using the principal component analysis-based classification defined in a previous study using POFC subjects (Leslie et al, 2016).…”
Section: Genome Wide Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…This was clearest for East African individuals, which is unsurprising due to the higher divergence in allele frequency and linkage disequilibrium between African and non-African populations ( 93 ). Furthermore, a recent GWAS of nsCL/P risk from multiple broad ancestry groups found substantial dependence on ancestry in terms of SNP effect size and significance ( 109 ).…”
Section: Common Variation In Craniofacial Shapementioning
confidence: 99%
“…Although many susceptibility loci have been suggested by linkage and candidate gene association studies, the vast majority were non replicable across studies 6 . A remarkable exception was IRF6 (interferon regulatory factor 6), in which heterozygous loss-of-function mutations lead to van der Woude syndrome and their association with NSCL/P was confirmed in several GWAS 7 . The IRF6 gene on chromosome 1q32.3-q41 encodes interferon regulatory factor 6, which is a key element in oral and maxillofacial problems and is one of the candidate genes associated with both syndromic and non-syndromic forms of clefts 8 .…”
Section: Introductionmentioning
confidence: 99%